Personnel Recruitment and Organizational Performance in Edo State Civil Service Edo State – Nigeria - Orumwense, Jones Osasuyi; Mwakipsile, Greenfield (Journal of Accounting, Business and Finance Research, 2017)
This study investigated on personnel recruitment and organizational performance in Edo civil service, Edo State – Nigeria. The study was guided by the following research objective: i) to investigate personnel recruitment at Edo State Civil, Edo State, Nigeria. ii) to determine the level of organizational performance at Edo State Civil Service, Edo State. iii) to examine the relationship between personnel recruitment and the level of organization performance at ESCS, Edo State. methodology, the study adopted descriptive cross-sectional survey research design, specifically cross-sectional survey design using both the quantitative and qualitative methods of data collection. Data was collected using questionnaires. Data analysis: data was analysed using Person’s correlation coefficient. Finding: the study revealed that personnel recruitment at Edo State Civil Service showed an average mean of (mean=3.22) and was interpreted as satisfactory while there was a high level of organization performance at ESCS with an average (mean-2.99) which was interpreted as satisfactory. The findings indicated a strong and positive correlation between personnel recruitment and the level of organization performance (r=0.942, Sing-=0.025). Conclusion: the recruitments needed when recruiting candidates. The researcher recommended that the human resource department- should have laid out recruitment policy that will guide the recruitment process. This would in turn guarantee efficiency in the selection procedures and provide an adequate pool of quality applicants.